Beyond Regulation: Proactive Financial Risk Management in an AI-Driven World - Gandhi, Anup Kumar (International Journal of Artificial Intelligence, Data Science, and Machine Learning, 2025)
The rapid integration of artificial intelligence (AI) in the financial sector has revolutionized operational efficiency and decision-making capabilities. However, the emergence of these technologies has also introduced novel risks that extend beyond the scope of traditional regulatory frameworks. This paper explores the necessity of transitioning from reactive, regulation-focused risk management to proactive approaches capable of addressing AI-specific challenges. By leveraging AI’s potential for real-time monitoring, predictive analytics, and dynamic adaptation, organizations can mitigate algorithmic biases, enhance cybersecurity measures, and uphold ethical standards. The study underscores the importance of a collaborative ecosystem, uniting regulators, financial institutions, and technology developers in fostering adaptive risk management practices. This shift not only strengthens organizational resilience but also ensures the sustainability of the financial system in an AI-driven world